2017
DOI: 10.1111/jace.14798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on TiO2 crystallization kinetics using in‐situ high‐temperature synchrotron radiation diffraction

Abstract: The phase transformation behavior of TiO 2 sol-gel synthesized nanopowder heated in a sealed quartz capillary from room temperature to 800°C was studied using in-situ synchrotron radiation diffraction (SRD). Sealing of the capillary resulted in an increase in capillary gas pressure with temperature. The pressures inside the sealed capillary were calculated using Gay-Lussac's Law, and they reached 0.36 MPa at 800°C. The as-synthesized material was entirely amorphous at room temperature, with crystalline anatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…The effect of doping and co-doping on anatase TEC was studied based on pure, In-doped, Al-doped, co-doped Ag–Cr, and co-doped In–Cr titania nanoparticles. Information on pure/undoped anatase nanopowder and that doped with In and (In–Cr) has been provided previously [ 33 , 35 , 36 ]. A sol–gel approach was taken using titanium (IV) isopropoxide (C 12 H 28 O 4 Ti, molecular weight of 284.22 g/mol, Sigma-Aldrich, New South Wales, Australia).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of doping and co-doping on anatase TEC was studied based on pure, In-doped, Al-doped, co-doped Ag–Cr, and co-doped In–Cr titania nanoparticles. Information on pure/undoped anatase nanopowder and that doped with In and (In–Cr) has been provided previously [ 33 , 35 , 36 ]. A sol–gel approach was taken using titanium (IV) isopropoxide (C 12 H 28 O 4 Ti, molecular weight of 284.22 g/mol, Sigma-Aldrich, New South Wales, Australia).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The transformation of anatase-to-rutile has been studied for 400–1200 °C [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but limited titania thermal-expansion data exist near the transition temperature. Titania thermal expansion has not been studied in detail and the effects of form, crystal structure, synthesis, doping, particles size, surface area, and atmospheric reactions from a high to a transition temperature are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal treatment of amorphous titania at elevated temperature yields, anatase, rutile, or a mixture of these crystalline structures as the most common titania phases, whereas brookite formation is rare [ 10 ]. Titania phase transformation is influenced by several conditions, such as calcining temperature, heating rate, calcination time, synthesis method, dopants, the level of impurities, grain size, and atmospheric condition and type [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, several works have studied the kinetic of structural transformation (anatase‐to‐rutile) in TiO 2 compound synthesized via different methodologies . In these studies, it has been observed that the stability of the anatase phase as well as the phase transition could be controlled by some parameters, such as precursor materials, annealing temperature, particle size, morphology, surface chemistry, and addition and concentration of impurities (dopants or caping agents) . According to literature, both the catalytic properties were proved to strongly depend on the crystalline structure, making the control of anatase‐to‐rutile transformation process becomes a key parameter for the development of devices operating with maximum performance …”
Section: Introductionmentioning
confidence: 99%
“…[35,[41][42][43][44][45][46][47][48][49][50] In these studies, it has been observed that the stability of the anatase phase as well as the phase transition could be controlled by some parameters, such as precursor materials, annealing temperature, particle size, morphology, surface chemistry, and addition and concentration of impurities (dopants or caping agents). [16,25,35,[44][45][46][48][49][50][51][52][53][54][55] According to literature, both the catalytic properties were proved to strongly depend on the crystalline structure, [23,31,34,36,42] making the control of anatase-to-rutile transformation process becomes a key parameter for the development of devices operating with maximum performance. [27,31,56] The addition of transition metals ions (e.g., Fe, Co, and Nb) into the TiO 2 lattice has been an efficient way to enhance the (photo) catalytic activity.…”
Section: Introductionmentioning
confidence: 99%